ENHANCEMENT OF GOVERNMENT INNOVATION POLICY IN DIGITAL TRANSFORMATION OF RUSSIAN COMPANIES - Veselovsky, Mikhail; Izmailova, Marina; Bitkina, Inna; Krasyukova, Natalia; Stepanov, Alexander (Revista Inclusiones, 2020)
The paper substantiates the problem of speeding up the digital transformation of the Russian economy based on large-scale support from the government. Key determinants in the emergence and advance of the Russian digital economy are identified. Overviews of the Russian Internet economy are provided, based on appraisals by Russian and foreign experts. The main cited problems hindering the development of the digital economy in Russia include: digital inequality of Russian regions, skills shortage in the IT industry, inadequate investment in the digital development of business, inadequate legal framework in electronic commerce and intellectual property protection with regard to digital content. An analysis of Russian business leaders’ views regarding the level of maturity of digital development in their companies is offered. Relevant directions of digital project implementation in Russian companies are established. A comparative analysis of digital practices depending on company size and industry is conducted. A direct link is established between the company size and digital activity growth, as well as between digital development directions and the industry. A conclusion is drawn that Russian businesses recognise the need to build business processes powered by digital technology.